Meningioma of foramen magnum - Benedek, Pedro; De Tenyi, Andrés; Bonnevaux de Toma, Stella; Purriel, Juan; Pol Deus, Jorge; Ghizoni, Marcos (Cirugía del Uruguay, 1979)
The authors describe a case of foramen magnum meningioma of the spinocranial type. Clinical, radiological and surgical findings are presented. The need of an adequate surgical exposure of the tumor and of a complete excision without damage to the brain possible nowadays by means of a microneurosurgical technique- are underlined.